I codici Casin. 98 e 99: la tradizione omiletica a Montecassino all’epoca dell’abate Desiderio - Casavecchia, Roberta (Scrineum, 2013)
The contribution focuses on the analysis of two 11th-century homiliaries (Casin. 98 and 99) produced at Montecassino under the abbot Desiderius (1058-1087), both especially well known for the high quality of their decoration (Casin. 99 also for the valuable information conveyed by its colophon). The article offers detailed descriptions of both codices, and a thorough identification of the texts they contain. The composition of the two collections, focusing on the main feasts of the two great liturgical cycles (Temporale and Santorale), is examined within the wider framework of the homiletic production in Beneventan script. Casin. 98 also contains a sermon by Peter Chrysologus, added at the beginning of the original codex, which raises questions about its possible identification with the Sermones Severiani which are mentioned in the book catalogue reported by the Chronica Monasterii Casinensis. Moreover, the loss of most of the leaves containing decorated initials allows to formulate an hypothesis of reconstruction of the original structure of the codex.